ANALISIS PENGARUH PENDAPATAN KOPERASI, SIMPANAN POKOK, SIMPANAN WAJIB, SIMPANAN SUKARELA DAN PINJAMAN ANGGOTA TERHADAP SISA HASIL USAHA - Sri Rahayu, Witji (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This research was conducted with the aim of knowing the analysis of the effect of cooperative income, principal savings, mandatory savings, voluntary savings and member loans on the remaining operating results at KSP Kharisma Nganjuk district. The hypothesis was tested using time series data assisted by microsoft excel 2007 and Stata for windows version 16. The method used is a quantitative approach with secondary data, namely the financial statement of KSP Kharisma Nganjuk regerency for the period 2019 – 2021. The results of this study are that cooperative income has a long term effevt on the remaining operating results, principal savings have a long term effect on the remaining operating results, mandatory savings have a long term effect on the remaining operating results, voluntary savings have a long term effect on the remaining operating results and member loans have a long term effect on the remaining operating results. With the probability value of cooperative income 0,0000 < 0,05, the probability value of principal savings 0,0082 < 0,10, the probability value of mandatory savings 0,0025 < 0,05, the probability value of voluntary savings 0,0003 < 0,05 and the probablity value of member loans 0,000 < 0,05.